(untitled) (Sociologisk Forskning, 2002)
The juridification of conflicts among juveniles In the last few years, we have witnessed an increasing tendency in Sweden to submit conflicts among juveniles to the legal system. In this article, I address issues concerning the process and consequences of juridification of conflicts in this group. The legal system is a relatively autonomous system, but it is also open for other discourses. The article uses discourse analysis, in an attempt to unravel both how the legal system operates to redefine everyday events in legal terms, and how extraneous, racialized discourses make their way into court. In this sense, it also sets out to trace how stratification is reproduced and permeated by the legal system. The empirical material consists of an analysis of a trial between two juveniles, Lars and Moustafa. Apart from legal documents pertaining to the case, I also make use of observation notes from trial, and the analysis is supplemented with newspaper materials from the period. The analysis describes how the legal system transforms and redefines the juveniles’ comprehension of an event into the categories and internal logic of the legal system. It also uncovers how media and scientific discourse helps to shape the court’s construction and deconstruction of the conflict.